(untitled) (IIUC Business Review, 2022)
Automation has started its journey in every area after the invention of computer. Accounting is a traditional discipline from a long period of time. A rigorous development in this field has taken place in the last few decades. Now-a-days all of the functions of this discipline are almost automated. Specially, financial reporting is a crucial issue and is required by various stakeholders timely and accurately. Computerised system can ensure these qualities of financial reports. For conducting the study, data were collected by using questionnaire. Collected data were analyzed by using SPSS (version 22). KMO, factor analysis, ANOVA, regression, etc. are done on the collected and coded data. A lot of benefits of automated reports have been revealed like time-saving, cost-effective, increasing the speed and efficiency along with some challenges. The major challenges include maintaining security and the massive investment which is required for installing an automated system. Some policy implications from both bankers and customer-views are suggested to make the system sophisticated by ensuring the protection of the system. IIUC Business Review Vol. 9, Dec. 2020 pp. 77-102